From struggles to strategies: Indonesian students’ use of e-portfolios in public speaking courses through the lens of self-regulated learning and sociocultural theory - Raden Muhammad Ali; Pamastu Narpaduita; Muhammad Iqwan Sanjani; Ummi Khaerati Syam; Dwi Hastuti; Muhammad Kunta Biddinika (Universitas Muhammadiyah Sidoarjo, 2025)
The implementation of e-portfolios in education has gained recognition as both an assessment and a learning tool. This descriptive qualitative study examines the challenges faced by students in creating electronic portfolios (e-portfolio) using Google Sites, consisting of speech drafts, recorded presentations, reflection notes, and peer feedback, and the strategies they employed to overcome these challenges. This study involved 22 English Education students enrolled in a public speaking course at a university in Yogyakarta, Indonesia, including eight participants who were interviewed. Data were collected through observations, semi-structured interviews, and documentation. The findings highlight three major challenges: technical barriers (digital skills and internet access), time management difficulties, and creativity-related issues. These findings are interpreted through the lenses of self-regulated learning theory and sociocultural theory, which explain how learners manage their own learning and benefit from peer and lecturer support. To address these challenges, students employed peer collaboration, self-directed learning strategies, and time management techniques. The study offers insights for designing e-portfolio-based speaking courses in similar EFL contexts by systematically addressing obstacles while fostering learner autonomy, creativity, and responsibility. Practically, it provides guidance for lecturers to scaffold e-portfolio tasks and integrate peer collaboration effectively. Methodologically, it demonstrates the application of thematic analysis in e-portfolio research. Theoretically, it links e-portfolio use with self-regulated learning and sociocultural theory.